Floristic and ecological characterization of habitat types on an inselberg in Minas Gerais, southeastern Brazil - Paula, Luiza F. A. de; Mota, Nara F. O.; Viana, Pedro L.; Stehmann, João R. (Acta Botânica Brasílica, 2017)
ABSTRACT Inselbergs are granitic or gneissic rock outcrops, distributed mainly in tropical and subtropical regions. They are considered terrestrial islands because of their strong spatial and ecological isolation, thus harboring a set of distinct plant communities that differ from the surrounding matrix. In Brazil, inselbergs scattered in the Atlantic Forest contain unusually high levels of plant species richness and endemism. This study aimed to inventory species of vascular plants and to describe the main habitat types found on an inselberg located in the state of Minas Gerais, in southeastern Brazil. A total of 89 species of vascular plants were recorded (belonging to 37 families), of which six were new to science. The richest family was Bromeliaceae (10 spp.), followed by Cyperaceae (seven spp.), Orchidaceae and Poaceae (six spp. each). Life forms were distributed in different proportions between habitats, which suggested distinct microenvironments on the inselberg. In general, habitats under similar environmental stress shared common species and life-form proportions. We argue that floristic inventories are still necessary for the development of conservation strategies and management of the unique vegetation on inselbergs in Brazil.